Macromol. Mater. Eng. 8/2016. Issue 8 (5th August 2016) - Xu, Zewen; Mahalingam, Sunthar; Basnett, Pooja; Raimi‐Abraham, Bahijja; Roy, Ipsita; Craig, Duncan; Edirisinghe, Mohan
Abstract : Front Cover: Pressurised melt gyration is a novel solvent‐free process which manufactures suitably doped non‐woven polymeric fibres for healthcare applications such as antibacterial and tissue engineering. Polymer jetting through coarse holes in the gyrating pot creates fibres. Their size can be controlled using gyration speed, temperature and pressure. Further details can be found in the article by Zewen Xu, Sunthar Mahalingam, Pooja Basnett, Bahijja Raimi‐Abraham, Ipsita Roy, Duncan Craig and Mohan Edirisinghe* on page 922.